(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Analysis of literature data shows the scale and significance of the problem of intestinal invasions. The harm caused by intestinal parasites to the developing body of a child undoubtedly cannot be underestimated. The primary condition in solving this problem is the development of modern, comprehensive methods for diagnosing intestinal parasitoses, as well as taking into account the immaturity of the child’s immune system, the development of an algorithm for antiparasitic measures before routine vaccinations of children.